Towards a general theory of perspective taking - Stålne, Kristian (Transdisciplinary journal of engineering & science, 2025)
Perspective taking is emphasized by several developmental theorists as a basic aspect of human development, although it hasn’t been properly defined beyond the conventional stages and 3rd person perspective. The aim of this analysis is to present a general theory of perspective taking, introduce six orders of perspective taking and apply them to the psychological, relational and physical aspects of reality. The analysis is formulated from principles of adult development and compared with stage descriptions of social perspective taking according to Selman, children’s understanding of space according to Piaget and Inhelder and stage descriptions from Ego development theory by Cook-Greuter. This theoretical formulation of perspective taking allows for generalization into an understanding of physical reality according to 4th and 5th person perspectives with examples in Einstein’s theory of special and general relativity and quantum mechanics, according to Bohr.